Building Working Alliance on Online and Offline Counselling - Hafnia Rahma Alifa; Suci Nugraha; Endah Nawangsih (Humanities, Society, and Community, 2024)
Telecounseling in Indonesia can be a solution to overcome the shortage of mental health professionals to address psychological problems. Telecounseling is a new challenge for psychologists. The high public interest in using telecounseling has not been accompanied by empirical data on the challenges psychologists face in providing online counseling services, especially in establishing working alliances as a key competency for building therapeutic relationships. The purpose of this study was to understand counselor competencies in building working alliances in online and offline psychological services. Participants in this cross-sectional study were 93 counselors selected by simple random sampling. The measurements were conducted using the Indonesian version of the Therapist Interpersonal Skill Scale. In general, the counselor’s ability to provide online counseling was lower (79.58%) than when providing offline counseling (96.8%). The differences in counselors’ abilities covered all three aspects of the working alliance measured, namely 1) extra-therapeutic influence, 2) therapy skills, and 3) perception of outcomes. Because this research is cross-sectional, it can only analyze the characteristics of respondents in one-time period, but it does offer empirical data about the differences in counselor ability to build working relationships in online and offline counseling.